A Survey on Artificial Intelligence Role in Transforming English Language Teaching - Patrick Mthethwa; Sithembile Hlatshwayo; Nkosinathi Sibandze (Journal of Research in Education and Pedagogy, 2025)
Artificial Intelligence (AI) has emerged as a powerful educational tool, offering innovative solutions to enhance learning outcomes across various disciplines. No reasonable explanation can convince today’s generation to ignore artificial intelligence in their educational and social practices. In the realm of English language education, AI technologies are revolutionizing traditional teaching methods, providing personalized learning experiences while preparing learners for the demands of the globalized world. This study explored the role of artificial intelligence in transforming English language teaching in the context of Eswatini. The main objective was to establish teachers’ views on the role of AI in language teaching. The study adopted a concurrent mixed-methods design, consisting of twelve (12) consenting participants. An open-ended questionnaire was used to collect data, which was later coded to allow inductive categories to emerge. Content analysis was used as a data analysis method. Furthermore, the qualitatively analyzed data were transformed into numerical values and were subjected to SPSS for descriptive statistics, mainly frequencies. The findings revealed that participants view AI as a helpful educational tool that could be used for English language teaching. The findings also revealed polarized views regarding whether or not AI is helpful. Some participants think AI is not helpful, and they will not use it for teaching. Others lament the fact that they are unfamiliar with AI and cannot use it in teaching. Based on the main findings, the study concludes by noting the value of using AI in English language teaching. There is a need for the adoption of AI to support English language teaching, especially in developing countries. These findings have implications for teaching and the development of an AI policy framework focusing on improving language teaching.